CO detection equipment based on unmanned aerial vehicle, NiCo2O4 / Ti3C2 MXene composite material contained in CO detection equipment and preparation method
By integrating NiCo2O4/Ti3C2 MXene heterostructures through hydrothermal synthesis and UAV platform integration, the problems of low sensitivity and high power consumption of UAV CO gas sensors have been solved, achieving high-sensitivity and low-power CO detection and promoting the development of intelligent environmental monitoring systems.
Patent Information
- Application Number
- CN202511222862.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-12-02
AI Technical Summary
Existing CO gas sensors on UAV platforms suffer from low sensitivity, high power consumption, and poor stability, which limits their application in environmental monitoring.
A NiCo2O4/Ti3C2 MXene heterostructure is used as the CO sensor material and prepared by hydrothermal synthesis. Combined with circuit board design, it provides high-sensitivity and low-power CO detection for UAV platforms, including a CO sensor module, a power management module, and a voltage divider measurement module. The circuit board adopts a circular design and double-sided copper plating to reduce noise interference.
It achieved a response of 139.5% to 100ppm CO at 110℃ with a response time of 39 seconds, and can generate a real-time three-dimensional gas distribution map within 3 minutes, meeting the low energy consumption requirements of UAV platforms.
Smart Images

Figure CN121049458A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gas sensor technology, specifically relating to a CO detection device based on a drone, the NiCo2O4 / Ti3C2 MXene composite material contained therein, and the preparation method thereof. Background Technology
[0002] With the acceleration of industrialization and urbanization, carbon monoxide (CO), a colorless, odorless, and tasteless toxic gas, poses a serious threat to public health. As a major byproduct of vehicle exhaust and industrial combustion, carbon monoxide binds to hemoglobin, leading to systemic hypoxia and triggering a series of pathological reactions. Traditional CO monitoring methods have limitations, such as the inability of fixed-point monitoring to achieve large-scale and rapid monitoring, and the insufficient accuracy and stability of portable devices. Therefore, there is an urgent need to develop a new CO detection method with a wider detection range, stronger real-time performance, lower labor costs, and good environmental adaptability. As an emerging technological means, unmanned aerial vehicles (UAVs) have been widely used for aerial mapping of hazardous chemicals in the environment due to their flexibility and efficiency, enabling functions such as threat detection and ozone neutralization mapping. In recent years, the combination of UAVs and gas sensors for gas detection has become an efficient, flexible, and cost-effective monitoring method, bringing new breakthroughs to the field of environmental monitoring.
[0003] However, the integration of existing CO gas sensors into UAV platforms still faces many challenges. For example, commercially available tin dioxide (SnO2)-based CO sensors have detection limits higher than 10 ppm and require operation at high temperatures of 200-400°C, which not only fails to meet the low-energy requirements of UAVs but also increases their energy consumption burden. Furthermore, Ahlawat et al. investigated the performance of a lightweight gas sensor system (LWGSS) for UAV applications and found that the CO gas sensor within it exhibited poor correlation (R0). 2 =0.44, slope =0.98). Liu et al. first used LaNbO4 as the electrode material for a mixed-potential carbon monoxide (CO) gas sensor, which exhibited the most comprehensive CO sensing characteristics at an operating temperature of 400°C. However, its high-temperature operation requirements resulted in excessive power consumption, making it unsuitable for drone applications where power consumption and weight are extremely sensitive. Although drone-borne sensors have shown great potential in environmental monitoring, the low sensitivity, high power consumption, and poor stability of existing CO sensors limit their integration and application on drone platforms.
[0004] Therefore, developing a real-time CO monitoring device based on unmanned aerial vehicles (UAVs) is of great significance in the field of gas sensor technology. Summary of the Invention
[0005] In view of this, this invention first developed a novel NiCo2O4 / Ti3C2 MXene heterostructure via hydrothermal synthesis for highly sensitive carbon monoxide (CO) detection, achieving a response of 139.5% to 100 ppm CO at 110 °C with a response time of 39 seconds. Subsequently, the NiCo2O4 / Ti3C2 MXene heterostructure was integrated into a micro-UAV platform, enabling real-time three-dimensional gas distribution mapping within 3 minutes. This is the first time such a heterostructure has been used for UAV-based CO monitoring. This work not only advances the fundamental understanding of MXene-based gas sensing mechanisms but also provides a practical blueprint for intelligent environmental monitoring systems, bridging the gap between nanomaterial development and applications in urban air quality assessment, industrial emissions tracking, and public health protection.
[0006] To achieve the above objectives, the first objective of this invention is to provide a CO detection device based on an unmanned aerial vehicle (UAV), employing the following technical solution:
[0007] A CO detection device based on a drone, the circuit board includes a CO sensor module, a power management module, a sensor heating module and a voltage divider measurement module, the CO sensor module is made of NiCo2O4 / Ti3C2 MXene composite material, and the voltage of the sensor heating module and the voltage divider measurement module is 3V.
[0008] It is worth noting that MXene materials possess high electrical conductivity, large specific surface area, and abundant surface functional groups, making them excellent in gas adsorption and transport. These unique properties of MXene bring new opportunities for improving the performance of gas sensors. However, pure MXene-based gas sensors still have some limitations, including high carrier recombination rates, low response, and slow response / recovery speeds to target gases. These factors hinder their development in gas sensing applications.
[0009] To address the insufficient sensitivity of current MXene-based sensors in detecting carbon monoxide (CO), combining MXene with metal-oxide-semiconductor (MOS) technology to enhance gas sensing performance has become an effective approach. Nickel-cobalt oxide (NiCo2O4) is a p-type bimetallic semiconductor. Its multivalent metal center (Ni...) 2+ / Ni 3+ and Co 2+ / Co 3+In synergy with oxygen vacancies, NiCo2O4 effectively promotes the adsorption and activation of CO molecules through a dynamic redox mechanism, thereby improving the sensitivity of the gas sensor. By synthesizing NiCo2O4 and MXene, the advantages of both can be fully utilized to achieve a synergistic effect, thus significantly improving the performance of the gas sensor. With this in mind, this invention uses a NiCo2O4 / Ti3C2 MXene composite material, combining their respective advantages to achieve a synergistic effect, as the core sensing material for a carbon monoxide (CO) sensor mounted on an unmanned aerial vehicle (UAV).
[0010] Furthermore, conventional semiconductor gas sensors typically employ 5V heating and voltage divider circuits. To adapt to the low-voltage and low-power characteristics of UAV systems, this invention reduces both the heating module voltage and the voltage divider measurement module voltage to 3V.
[0011] Furthermore, the circuit board is a circular circuit board with double-sided copper plating, and the CO sensor module has a diameter of 34mm and a weight of 15g.
[0012] It is worth noting that the present invention uses a circular circuit board design to minimize the weight of the circuit board and reduces noise signal interference by double-sided copper plating.
[0013] Furthermore, to accommodate the stringent constraints of drones on size and payload, the CO sensor module used in this invention features a compact design with a diameter of only 34 mm and a weight of only 15 grams (including the connector), allowing it to be directly integrated into space-constrained drone platforms.
[0014] A second objective of this invention is to provide a NiCo2O4 / Ti3C2 MXene composite material contained in the CO detection device based on a drone as described above.
[0015] It is worth noting that drones have strict limitations on payload and limited energy. The lightweight properties of the NiCo2O4 / Ti3C2 MXene composite material make it suitable for drones to carry. Furthermore, this composite material maintains high sensitivity even with low power consumption, meeting the energy requirements of drones. The composite material's fast response time (39 seconds) also meets the drone's need to quickly acquire gas distribution information.
[0016] Furthermore, the composite material is a composite of bimetallic oxide NiCo2O4 and two-dimensional layered Ti3C2 MXene.
[0017] It is worth noting that NiCo2O4 is a p-type bimetallic semiconductor, while MXene is a two-dimensional layered material with high electrical conductivity, large specific surface area, and abundant surface functional groups. The two-dimensional layered structure facilitates rapid gas adsorption and desorption. Therefore, this invention employs a heterogeneous structure design to effectively improve the CO detection performance of the composite material.
[0018] A third objective of this invention is to provide a method for preparing the NiCo2O4 / Ti3C2 MXene composite material as described above.
[0019] A method for preparing NiCo2O4 / Ti3C2 MXene composite material, firstly by preparing multilayer Ti3C2T by acid etching. x MXene nanosheets were then processed to obtain NiCo2O4 / Ti3C2 MXene composite materials via a hydrothermal reaction.
[0020] Furthermore, the acid etching method is used to prepare multilayer Ti3C2T x Methods for using MXenes nanosheet materials include:
[0021] (1) Add 40% hydrofluoric acid to the reactor, control the temperature and homogenize, then slowly add Ti3AlC2 powder to make the concentration of the reaction system 0.1g / mL, and stir to carry out the etching reaction;
[0022] (2) After the etching reaction was completed, the black solution was centrifuged, the precipitate was washed with deionized water, the precipitate was dehydrated with ethanol, and dried to obtain multilayer Ti3C2T. x MXenes nanosheet materials.
[0023] Furthermore, the method for obtaining the NiCo2O4 / Ti3C2 MXene composite material through the hydrothermal reaction includes:
[0024] Urea and NH4F were dissolved in n-butanol to form a homogeneous solution. Ni(Ac)2 and Co(Ac)2 were then added to the solution, followed by homogenization. During homogenization, 1-10 wt% Ti3C2T (based on the mass of NiCo2O4) was added dropwise. x After the MXenes material is completely dissolved, it is hydrothermally reacted at 180℃ for 18-20 hours. After cooling to room temperature, the precipitate is repeatedly washed with deionized water and anhydrous ethanol and dried to obtain the NiCo2O4 / Ti3C2 MXene composite material.
[0025] Furthermore, the mass ratio of urea to NH4F is 1:1, and the concentration of urea in the n-butanol solution is 25 mg / mL; the molar ratio of Ni(Ac)2 to Co(Ac)2 is 1:2, and the ratio of the total mass of Ni(Ac)2 and Co(Ac)2 to the total mass of urea and NH4F is 1:2.
[0026] It is worth noting that this invention designs a heterostructure composite material based on NiCo2O4 / Ti3C2 MXene. This structural design can fully utilize the advantages of NiCo2O4 and Ti3C2 MXene to achieve a synergistic effect. NiCo2O4 has abundant oxidation states, which can regulate the electronic structure of the material, thereby enhancing its CO adsorption capacity. Ti3C2 MXene, on the other hand, has high electrical conductivity, a large specific surface area, and abundant surface functional groups, which can effectively improve gas adsorption and transport efficiency. This heterostructure design significantly improves the gas-sensing performance of the composite material.
[0027] Furthermore, the NiCo2O4 / Ti3C2 MXene composite material synthesized by the hydrothermal method in this invention possesses a porous structure, achieving microstructure optimization. This porous structure not only increases the specific surface area but also provides more charge transport channels, thereby improving charge transport efficiency. In addition, the porous structure prevents particle aggregation, exposes more active sites, and shortens ion diffusion paths, further optimizing the microstructure of the composite material. Simultaneously, in preparing the composite material, this invention selects lightweight Ti3C2 MXene as the base material and further reduces the weight of the composite material by optimizing its content, ensuring that the composite material maintains high performance while achieving lightweight design.
[0028] To ensure the integration of the composite material sensor with the drone, this invention also features a compact design for the CO sensor module. The entire CO sensor module is only 34mm in diameter and weighs only 15 grams, with the entire drone-mounted sensor system consuming only 220mW. This compact, low-power design allows the sensor module to be directly integrated into space-constrained drone platforms, achieving lightweight design.
[0029] Compared with existing technologies, this invention develops a novel NiCo2O4 / Ti3C2 MXene heterostructure via hydrothermal synthesis for highly sensitive carbon monoxide (CO) detection, achieving a 139.5% response to 100 ppm CO at 110 °C with a response time of 39 seconds. This performance improvement stems from the synergistic effect between NiCo2O4 and MXene, where density functional theory (DFT) calculations reveal a reduction in CO adsorption energy, while in-situ Raman spectroscopy directly observes the reversible CO chemisorption / desorption process at the heterostructure interface. Subsequently, the sensor was integrated into a micro-UAV platform, enabling real-time three-dimensional gas distribution mapping within 3 minutes. This is the first time such a heterostructure has been used for UAV-based CO monitoring. This work not only advances the fundamental understanding of MXene-based gas sensing mechanisms but also provides a practical blueprint for intelligent environmental monitoring systems, bridging the gap between nanomaterial development and applications in urban air quality assessment, industrial emissions tracking, and public health protection. Attached Figure Description
[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0031] Figure 1 The results of density functional theory (DFT) calculations for the NiCo2O4 / Ti3C2 MXene heterostructure in Experimental Example 1 of this invention are shown below. A) Optimal adsorption configurations of CO on the surfaces of NiCo2O4 (111), Ti3C2O2 MXene (006), and NiCo2O4 / Ti3C2O2 MXene; B) Adsorption energies of CO on Ti3C2O2 MXene, NiCo2O4, and NiCo2O4 / Ti3C2O2 MXene; C) Differential charge diagram of the most stable configuration of CO on NiCo2O4 / Ti3C2O2 MXene.
[0032] Figure 2The following are structural characterizations of the materials in Experimental Example 2 of this invention: a) SEM image of NiCo2O4; b) SEM image of Ti3C2MXene; c) TEM image of NiCo2O4 / Ti3C2MXene; d) EDS elemental mapping of NiCo2O4 / Ti3C2MXene; e) HRTEM image of NiCo2O4 / Ti3C2MXene; f) XRD patterns of Ti3C2MXene, NiCo2O4, and NiCo2O4 / Ti3C2MXene; g) N2 adsorption-desorption isotherms of NiCo2O4 and (h) NiCo2O4 / Ti3C2MXene, with the inset showing the pore size distribution curve; i) Thermogravimetric analysis curve of the NiCo2O4 / Ti3C2MXene composite material.
[0033] Figure 3 The X-ray photoelectron spectroscopy (XPS) of Ti3C2 MXene, NiCo2O4 and NiCo2O4 / Ti3C2 MXene nanocomposites in Experimental Example 2 of this invention are shown in the following diagrams: a) full spectrum, b) C 1s spectrum, c) O 1s spectrum, d) Co 2p spectrum, e) Ni 2p spectrum, and f) Ti 2p spectrum.
[0034] Figure 4 The following are the gas-sensing performance test results for Experiment 3 of this invention, including: a) the response of NiCo2O4 and NiCo2O4 / Ti3C2-5 to 100ppm CO at different temperatures; b) the sensitivity of NiCo2O4 / Ti3C2-1, NiCo2O4 / Ti3C2-3, NiCo2O4 / Ti3C2-5, NiCo2O4 / Ti3C2-8, and NiCo2O4 / Ti3C2-10 composite materials to 100ppm CO at the same temperature; c) the response and recovery time of Ti3C2MXene, NiCo2O4, and NiCo2O4 / Ti3C2-5 to 100ppm CO at the optimal temperature of 110℃; d) the response of NiCo2O4 and NiCo2O4 / Ti3C2-5 to different CO concentrations; e) the resistance change of the sensor when exposed to 10-1000ppm CO; f) the linear fitting curve of response versus concentration; and g) the sensor's response to 100ppm CO at 110℃. h) Repeatability curve of CO; i) Response stability of the sensor over 30 consecutive days; j) Selective response of the sensor to different gases.
[0035] Figure 5This is a schematic diagram of the gas sensing mechanism and in-situ Raman spectroscopy characterization of the materials in Experimental Example 4 of this invention. Specifically, a) is a schematic diagram of the CO sensing mechanism of the heterostructure; e) is the in-situ Raman spectrum (200 to 600 cm⁻¹) of Ti₃C₂ MXene, NiCo₂O₄, and NiCo₂O₄ / Ti₃C₂ MXene during the CO sensing response and recovery process at 110°C and 100 ppm CO. -1 ).
[0036] Figure 6 The following is a structural and performance characterization of the CO detection device based on a UAV in Experiment Example 5 of this invention, including: a) circuit diagram of the power management and current-voltage (IV) sensing part of the UAV; b) size comparison of the sensing part of the device with a Chinese 1 yuan coin; c) top view and bottom view of the UAV; d) experimental principle diagram; e) depth map of the gas source by the binocular camera at different distances; f) flight trajectory and real-time resistance change of the UAV.
[0037] Figure 7 This is a schematic diagram of the CO sensing mechanism of the CO detection device based on a drone disclosed in this invention. Detailed Implementation
[0038] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0039] The term "embodiment" used herein, as an example, is not necessarily to be construed as superior to or better than other embodiments. Performance testing in the embodiments of this application, unless otherwise specified, employs conventional testing methods in the art. It should be understood that the terminology used in this application is merely for describing particular implementations and is not intended to limit the scope of this disclosure.
[0040] Unless otherwise stated, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; other experimental methods and technical means not specifically mentioned herein refer to experimental methods and technical means commonly used by one of ordinary skill in the art.
[0041] To better illustrate the content of this application, numerous specific details are provided in the following detailed embodiments. Those skilled in the art should understand that this application can be implemented even without certain specific details. In the embodiments, some methods, means, instruments, and devices well-known to those skilled in the art are not described in detail in order to highlight the main points of this application.
[0042] Without conflict, the technical features disclosed in the embodiments of this application can be combined arbitrarily, and the resulting technical solution belongs to the content disclosed in the embodiments of this application.
[0043] This invention discloses a drone-based CO detection device, the NiCo2O4 / Ti3C2MXene composite material used therein, and its preparation method, belonging to the field of gas sensor technology. This invention develops a novel NiCo2O4 / Ti3C2MXene heterostructure via hydrothermal synthesis for high-sensitivity carbon monoxide (CO) detection, achieving a response of 139.5% to 100 ppm CO at 110 °C with a response time of 39 seconds. This performance improvement stems from the synergistic effect between NiCo2O4 and MXene, where density functional theory (DFT) calculations reveal a decrease in CO adsorption energy, while in-situ Raman spectroscopy directly observes the reversible CO chemisorption / desorption process at the heterostructure interface. Subsequently, the sensor was integrated into a micro-drone platform, enabling real-time three-dimensional gas distribution mapping within 3 minutes. This is the first time such a heterostructure has been used for drone-based CO monitoring. This work not only advances the fundamental understanding of MXene-based gas sensing mechanisms but also provides a practical blueprint for intelligent environmental monitoring systems, bridging the gap between nanomaterial development and applications in urban air quality assessment, industrial emission tracking, and public health protection.
[0044] To better understand the present invention, the following embodiments are provided for further detailed description of the present invention, but they should not be construed as limiting the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above-described invention are also considered to fall within the protection scope of the present invention.
[0045] Example 1
[0046] First, take a clean plastic beaker and add an appropriate amount of stir bar. Then, add 20 mL of 40% hydrofluoric acid to the beaker and start stirring. Next, weigh 2.0 g of Ti3AlC2 powder and gradually add it to the etching reagent using a plastic spoon. After all the Ti3AlC2 has been added, cover the beaker, leaving only a vent hole. Continue stirring for 18 to 72 hours; the etching reaction is usually completed in 18 hours. After the etching reaction is complete, centrifuge the black solution to separate the precipitate. Discard the supernatant and retain the precipitate. Wash the precipitate with deionized water and repeat the centrifugation process until the pH of the supernatant after the last centrifugation is greater than 6. Finally, collect the bottom precipitate, dry it, and the resulting black powder is the multilayer Ti3C2T. xMXenes nanosheet material. Then, 1 g of urea and 0.5 g of NH4F were dissolved in 40 mL of n-butanol to form a homogeneous solution. Subsequently, 0.5 g of Ni(Ac)2 and 1 g of Co(Ac)2 were added to the above solution to prepare Ti3C2T. x MXene nanosheets were added dropwise during stirring at a rate of 5 wt% of the NiCo₂O₄ mass. The mixture was then vigorously stirred for 30 minutes to ensure complete dissolution and homogeneity. The resulting solution was then transferred to a 50 mL Teflon-lined stainless steel autoclave. The autoclave was sealed and the reaction was carried out at 180°C in an oven for 18 hours to promote the solvothermal reaction. After cooling to room temperature, the precipitate was filtered and repeatedly washed with deionized water and anhydrous ethanol to remove any residual reactants and byproducts. Finally, the resulting purplish-black precipitate was dried in an oven at 60°C to obtain the final product, NiCo₂O₄ / Ti₃C₂MXene, and the composite material was designated NiCo₂O₄ / Ti₃C₂-5.
[0047] Example 2
[0048] A drone-based CO detection device:
[0049] The schematic design, component selection, PCB layout, and production file generation of the sensor-UAV interface circuit board were all completed using EasyEDA software. The circuit board includes two 8-pin 2mm pitch headers for connecting and securing the sensor circuit board to the UAV body. This interface also supplies power from the UAV battery to the sensor motherboard and transmits the sensor's acquired signals to the UAV's STM32F4 main controller. It also includes a voltage divider detection circuit, based on an AD8606 instrumentation amplifier, connected in parallel at the midpoint of the series connection between the gas sensor and the matching resistor. This circuit measures the voltage across the matching resistor and transmits the detected voltage signal to the UAV's STM32F4 main controller via the header, indirectly measuring the voltage applied to the sensor and the sensor's resistance. A sensor heating circuit operating at 3V is also included. Conventional semiconductor gas sensors typically use 5V heating and voltage divider circuits. To accommodate the low-voltage, low-power characteristics of the UAV system, both the heating voltage and the voltage divider current supply voltage are reduced to 3V. The circuit board manufacturing process begins with designing the circuit schematic in EDA software, prioritizing low-power components within their package size. The PCB layout is designed for compactness, and a circular design minimizes weight. Double-sided copper plating reduces noise interference. After the PCB layout is complete, circuit patterns are fabricated on an insulating substrate using photolithography and etching processes. Components are then soldered onto the circuit board via reflow soldering. This circuit board integrates a NiCo2O4 / Ti3C2 MXene sensor module, a power management module, a sensor heating module, and a voltage divider measurement module, achieving highly sensitive detection of carbon monoxide gas.
[0050] Examples 3-6
[0051] The preparation of the NiCo2O4 / Ti3C2 MXene composite material was the same as in Example 1, except that the prepared Ti3C2T... x When MXenes nanosheets were added dropwise during stirring, the amounts added were 1 wt%, 3 wt%, 8 wt%, and 10 wt% of the mass of NiCo2O4, and the composite materials were designated as NiCo2O4 / Ti3C2-1, NiCo2O4 / Ti3C2-3, NiCo2O4 / Ti3C2-8, and NiCo2O4 / Ti3C2-10, respectively.
[0052] To further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following comparative examples and experimental examples further illustrate the properties and application performance of the NiCo2O4 / Ti3C2 MXene composite material disclosed in the present invention, its preparation method, and the CO detection equipment based on the UAV using it. However, these should not be construed as limiting the present invention. Other measurement experiments performed by those skilled in the art based on the above-described invention and the application based on the above properties are also considered to fall within the protection scope of the present invention.
[0053] Comparative Example 1
[0054] Ti3C2T x Preparation of MXenes materials:
[0055] First, take a clean plastic beaker and add an appropriate amount of stir bar. Then, add 20 mL of 40% hydrofluoric acid to the beaker and start stirring. Next, weigh 2.0 g of Ti3AlC2 powder and gradually add it to the etching reagent using a plastic spoon. After all the Ti3AlC2 has been added, cover the beaker, leaving only a vent hole. Continue stirring for 18 to 72 hours; the etching reaction is usually completed in 18 hours. After the etching reaction is complete, centrifuge the black solution to separate the precipitate. Discard the supernatant and retain the precipitate. Wash the precipitate with deionized water and repeat the centrifugation process until the pH of the supernatant after the last centrifugation is greater than 6. Finally, collect the bottom precipitate, dry it, and the resulting black powder is the multilayer Ti3C2T. x MXenes nanosheet materials.
[0056] Comparative Example 2
[0057] Preparation of NiCo2O4:
[0058] 1 g of urea and 0.5 g of NH4F were dissolved in 40 mL of n-butanol to form a homogeneous solution. Then, 0.5 g of Ni(Ac)2 and 1 g of Co(Ac)2 were added to the above solution. The mixture was then vigorously stirred for 30 minutes to ensure complete dissolution and homogeneity. The resulting solution was then transferred to a 50 mL Teflon-lined stainless steel autoclave. The autoclave was sealed and the reaction was carried out at 180 °C in an oven for 18 hours to promote the solvothermal reaction. After cooling to room temperature, the precipitate was filtered and repeatedly washed with deionized water and anhydrous ethanol to remove any residual reactants and byproducts. Finally, the resulting purplish-red precipitate was dried in an oven at 60 °C to obtain the final NiCo2O4 product.
[0059] Experimental Example 1: Gas Adsorption Mechanism
[0060] The fundamental mechanism of the NiCo2O4 / Ti3C2 MXene heterostructure was first determined through density functional theory (DFT) calculations. The MXene layers are typically terminated with oxygen (O), hydroxyl (OH), and fluorine (F) groups, forming distinct Ti3C2T layers. x Compounds. Oxygen-terminated MXene (Ti3C2O2) is more stable than fluorine-terminated MXene (Ti3C2F2) and hydroxyl-terminated MXene (Ti3C2(OH)2). For example... Figure 1 As shown in figure a, top-view and side-view models of the most stable configurations of NiCo2O4, Ti3C2O2 MXene, and NiCo2O4 / Ti3C2O2 MXene were constructed to deepen the understanding of the CO adsorption mechanism. Adsorption energy is an important parameter for measuring the adsorption strength of molecules on a material surface. Figure 1 As shown in b, the adsorption energy of NiCo2O4 / Ti3C2O2 MXene is more negative than that of NiCo2O4 and Ti3C2O2MXene, indicating that this heterostructure has a stronger adsorption capacity for CO, which helps to improve the response performance to CO. Further calculations were performed on the differential charge density map of the most stable adsorption configuration of CO on the NiCo2O4 / Ti3C2O2MXene surface. Figure 1 c). As can be seen, there is charge depletion near CO (blue area), while there is charge accumulation at the NiCo2O4 / Ti3C2O2 MXene interface (yellow area). This indicates that during adsorption, CO loses electrons, that is, CO releases electrons back into the conduction band of NiCo2O4 / Ti3C2O2 MXene, which is the basic principle of a type of gas-sensitive material for gas detection.
[0061] Example 2: Characterization of NiCo2O4 / Ti3C2 MXene heterostructure
[0062] The NiCo2O4, Ti3C2 MXene, and NiCo2O4 / Ti3C2Mxene materials prepared in Example 1, Comparative Examples 1 and 2 were characterized.
[0063] Figure 2 Image a shows scanning electron microscope (SEM) images of NiCo2O4 nanoparticles, revealing their irregular nanoparticle morphology and significant aggregation. In contrast, Figure 2 The Ti3C2 MXene in b exhibits a graphene-like multilayered nanostructure, forming bulk flakes. For example... Figure 2As shown in Figure c, the surface of the NiCo2O4 / Ti3C2 MXene composite material is significantly rough. NiCo2O4 nanoparticles not only cover the surface of Ti3C2 MXene but are also partially embedded between the Ti3C2 MXene layers. Furthermore, the NiCo2O4 nanoparticles expand the spatial gaps between the Ti3C2 MXene layers, which will facilitate the diffusion of gas molecules. Subsequently, the elemental distribution was analyzed using energy-dispersive X-ray spectroscopy (EDS). Figure 2 d) The elemental distribution of the prepared NiCo2O4 / Ti3C2 MXene heterostructure was analyzed. The uniform elemental distribution of Co, Ti, C, and Ni in the NiCo2O4 / Ti3C2 MXene heterostructure indicates that nano-sized NiCo2O4 is uniformly distributed on the surface of Ti3C2 MXene, and that the NiCo2O4 / Ti3C2 MXene heterostructure was successfully prepared. Figure 2 The image shows a high-resolution transmission electron microscope (HRTEM) image of the NiCo2O4 / Ti3C2 MXene heterostructure, in which lattice fringes and grain boundaries between NiCo2O4 nanoparticles and Ti3C2 MXene are clearly observed. Image analysis shows that the 0.47 nm lattice spacing matches the (111) crystal plane of cubic NiCo2O4, while the 0.27 nm spacing corresponds to the (006) crystal plane of Ti3C2 MXene, further confirming the complete bonding between NiCo2O4 nanoparticles and Ti3C2 MXene.
[0064] The crystal structure information of Ti3C2 MXene, NiCo2O4, and NiCo2O4 / Ti3C2 MXene heterostructures was characterized by X-ray diffraction (XRD). Figure 2As shown in f, the characteristic peaks observed in the XRD pattern of NiCo2O4 are located at 18.9°, 31.6°, 36.9°, 44.8°, 55.0°, 65.2°, 69.0°, and 79.3°, corresponding to the (111), (220), (311), (222), (400), (422), (511), and (440) crystal planes, respectively. The main diffraction peaks of MXene are located at 7.45°, 18.27°, 28.3°, and 60.81°, appearing on the (002), (004), (006), and (110) crystal planes, respectively, indicating that Ti3C2 MXene has a layered structure. The XRD pattern of the NiCo2O4 / Ti3C2 MXene heterostructure not only showed the characteristic diffraction peaks of NiCo2O4 but also those of Ti3C2 MXene, confirming the presence of both NiCo2O4 and Ti3C2 MXene in the composite material. These results indicate that NiCo2O4 / Ti3C2 MXene maintained their respective crystal structures in the nanocomposite without significant phase transitions or structural damage. Based on the characterization of the crystal structure and microstructure of NiCo2O4 and NiCo2O4 / Ti3C2 MXene, we performed N2 adsorption-desorption tests to analyze their specific surface area and pore structure (see...). Figure 2 The specific surface areas of pure-phase NiCo2O4 and NiCo2O4 / Ti3C2 MXene composite materials are 42.47 m² and 42.47 m², respectively. 2 / g and 49.16m 2 / g (calculated using the Brunauer-Emmett-Teller (BET) equation). Isotherm analysis showed that the composite material exhibited a typical Type IV isotherm with an H3 hysteresis loop, indicating a mesoporous structure. The corresponding average pore sizes were 13.81 nm and 10.67 nm, respectively. The increased specific surface area helps expose more active sites for gas adsorption and construct electron transport channels. Smaller pore sizes are more suitable for high-sensitivity detection of small molecule gases (such as H2 and CO). The synergistic effect between pore size and specific surface area is crucial for improving sensor performance. Thermogravimetric analysis (TGA) curves ( Figure 2 i) indicates that the initial mass loss of the NiCo2O4 / Ti3C2 MXene heterostructure in the low-temperature range is consistent with the desorption of physically adsorbed water molecules from the material surface. The mass loss continues to increase with increasing temperature, which may be due to component decomposition of the NiCo2O4 / Ti3C2 MXene composite at high temperatures. TGA results show that the NiCo2O4 / Ti3C2 MXene heterostructure maintains thermal stability at the sensor's operating temperature.
[0065] X-ray photoelectron spectroscopy (XPS) was used to analyze the chemical bonds and electronic states of Ti3C2 MXene, NiCo2O4, and NiCo2O4 / Ti3C2 MXene nanocomposites. Figure 3 a shows the full spectra of Ti3C2MXene, NiCo2O4, and NiCo2O4 / Ti3C2MXene. From Figure 3 In the full spectrum of a, characteristic peaks of Ni 2p, Co 2p, Ti 2p, O 1s and C 1s can be observed in the XPS spectrum of the NiCo2O4 / Ti3C2 MXene nanocomposite. Figure 3 b shows the C1s XPS spectra of Ti3C2MXene and NiCo2O4 / Ti3C2MXene. These spectra can be decomposed into four distinct peaks, corresponding to C-Ti, CC, CO, and C=O bonds, respectively. In the C1s spectrum of NiCo2O4 / Ti3C2MXene, the intensity of the C-Ti peak is reduced, which can be attributed to the disruption of the C-Ti bond due to the solvothermal reaction. Figure 3 As shown in Figure c, the O1s peak of NiCo2O4 / Ti3C2 MXene can be decomposed into three sub-peaks located at 531.3 eV, 531.7 eV, and 532.9 eV, respectively, corresponding to lattice oxygen (O2O4 / Ti3C2 MXene). L ), oxygen vacancy (O v ) and chemically adsorbed oxygen (O c Compared to NiCo2O4 alone, the NiCo2O4 / Ti3C2 MXene composite contains more oxygen vacancies (O2O4, Ti3C2 ... v The peak intensity of Ti3C2T increases. This indicates the introduction of Ti3C2T x MXene may increase the concentration of oxygen vacancies. Chemisorbed oxygen (O2) c The peak of ) was also increased in the NiCo2O4 / Ti3C2MXene composite material, which may mean that the introduction of Ti3C2MXene promoted the formation of chemisorbed oxygen. Figure 3 As shown in d, in the Co 2p spectrum of the NiCo2O4 / Ti3C2 MXene nanocomposite, we can observe Co 2p... 1 / 2 and Co 2p 3 / 2 The spin-orbit splitting peaks. These peaks further decompose into peaks related to Co. 2+ and Co 3+ Related peaks, of which Co 2+ The peak of Co is usually located at a lower binding energy, while Co 3+The peak is located at a higher binding energy. Furthermore, a satellite peak (Sat.) exists on the high binding energy side of the Co 2p3 / 2 peak, providing additional evidence for the oxidation state of cobalt. Comparing the spectra of the NiCo2O4 / Ti3C2 MXene composite with pure NiCo2O4 spinel, the Co 2p peak of the composite is similar to that of pure NiCo2O4 spinel, indicating that the oxidation state of cobalt remains stable in the composite, and the introduction of Ti3C2 MXene did not significantly alter the chemical state of cobalt. Figure 3 As shown in e, Ni 2p in the NiCo2O4 / Ti3C2 MXene composite material 3 / 2 and Ni 2p 1 / 2 The two peaks at 855.5 eV and 873.4 eV, respectively, confirm the presence of Ni in the composite material. The peaks at 861.6 eV and 880.1 eV belong to Ni 2p... 3 / 2 and Ni 2p 1 / 2 The shake-up satellite peaks. The Ti 2p spectrum of NiCo2O4 / Ti3C2MXene is shown below. Figure 3 As shown in f, two peaks are located at 455.3 eV and 459.7 eV, respectively. The peaks at 457.2 eV and 462.9 eV belong to Ti3C2MXene. 3+ 2p 3 / 2 and 2p 1 / 2 The orbitals, while the peaks at 455.8 eV and 461.5 eV belong to Ti. 2+ 2p 3 / 2 and 2p 1 / 2 Orbit. Ti in NiCo2O4 / Ti3C2 MXene composites 3+ The peak shifts towards higher binding energies, indicating the formation of a NiCo2O4 / Ti3C2 MXene heterostructure, which is related to electron loss. In summary, XPS analysis results show that the NiCo2O4 / Ti3C2 MXene nanocomposite successfully retains the crystal structure of NiCo2O4 while successfully introducing Ti3C2 MXene.
[0066] Experiment Example 3: Gas Sensing Performance Test
[0067] This invention first investigated the sensing performance of sensors based on NiCo2O4 and NiCo2O4 / Ti3C2 MXene heterostructures for carbon monoxide (CO) at different temperatures. Figure 4This study compared the responses of NiCo2O4 and NiCo2O4 / Ti3C2 MXene heterostructures (containing 5% MXene) to 100 ppm CO at different temperatures. The responses of both materials initially increased and then decreased with increasing temperature. This indicates that appropriate temperatures can enhance CO adsorption and diffusion on the material surface, thereby improving the sensor's response performance; however, excessively high temperatures may lead to CO desorption, thus reducing the response. At the optimal temperature of 110 °C, the response of the NiCo2O4-based sensor was only 27.1%, while the response of the NiCo2O4 / Ti3C2 MXene heterostructure reached as high as 139.5%. However, sensors based on NiCo2O4 / Ti3C2-1, NiCo2O4 / Ti3C2-3, NiCo2O4 / Ti3C2-8, and NiCo2O4 / Ti3C2-10, with Ti3C2 MXene contents of 1%, 3%, 8%, and 10%, respectively, showed response values of only 9.8%, 21.5%, 32.6%, and 93.7%. This indicates that the NiCo2O4 / Ti3C2 MXene heterostructure containing 5% MXene exhibits superior gas sensitivity (see...). Figure 4 b). Therefore, subsequent tests were conducted only on sensors based on NiCo2O4 / Ti3C2 MXene heterostructures containing 5% MXene. Figure 4 c compares the response and recovery times of Ti3C2 MXene, NiCo2O4, and the NiCo2O4 / Ti3C2 MXene heterostructure to 100 ppm CO at the optimal temperature of 110 °C. According to previously reported literature, pure Ti3C2 MXene shows almost no response to CO gas. In contrast, the sensor based on the NiCo2O4 / Ti3C2 MXene heterostructure exhibits a response time of 39 seconds and a recovery time of 234 seconds, which is superior to the NiCo2O4-based sensor (51 seconds / 257 seconds). This demonstrates that the sensing properties of the NiCo2O4 / Ti3C2 MXene heterostructure are significantly improved compared to NiCo2O4 and Ti3C2 MXene alone. The low response of the gas sensor based on NiCo2O4 nanoparticles to CO is mainly due to the low charge transport efficiency caused by nanoparticle aggregation and the reduced number of active sites available for CO molecule adsorption. The high conductivity of MXene facilitates efficient charge transport during sensing, thereby shortening the response and recovery times. Figure 4 Figure d shows the real-time response-recovery curves of NiCo2O4 and NiCo2O4 / Ti3C2MXene heterostructures at different CO concentrations. For the NiCo2O4 and NiCo2O4 / Ti3C2MXene heterostructures, the gas sensing response exhibits p-type semiconductor characteristics, i.e., the resistance increases when CO gas is introduced. Figure 4 The graph shows the resistance changes of the sensor when exposed to 10–1000 ppm CO. Clearly, the CO concentration affects the sensor's sensitivity. With increasing CO concentration, the response values of both materials increase, primarily due to the small accumulation of CO and the presence of numerous active sites. Figure 4 f shows the linear fitting curve of the sensor response versus CO concentration. The linear fitting equations for NiCo2O4 and NiCo2O4 / Ti3C2-5 are y = 0.298x + 6.26(R²). 2 =0.93695) and y = 1.53133x + 27.02667 (R 2 =0.95332). Both sensors exhibit good linearity in the 10-100 ppm CO concentration range, which facilitates the quantitative detection of CO gas.
[0068] From a practical application perspective, repeatability, stability, and selectivity are important parameters for evaluating gas sensors. For example... Figure 4 As shown in g, the sensor was injected with 100 ppm CO at 110 °C. The results show that the sensor exhibits stable response and recovery capabilities in multiple tests, demonstrating good repeatability and reliability for CO detection. Figure 4 h demonstrates the sensor's response stability over 30 days. The sensor's response remained relatively stable with only slight fluctuations, exhibiting good long-term stability and suitability for continuous CO detection. Figure 4 The selective response of the sensor to different gases, including SO2, C2H6, CH4, C3H8, CO, C2H4, and H2, was investigated. The sensor showed a significant response to CO, indicating that it has good selectivity and can distinguish CO from other interfering gases.
[0069] Experimental Example 4: Gas Sensing Mechanism
[0070] Based on the above results, this invention proposes a gas sensing mechanism for the NiCo2O4 / Ti3C2 MXene heterostructure. NiCo2O4 is a p-type semiconductor bimetallic oxide. In an air environment, oxygen molecules (O2) first undergo physical adsorption on the NiCo2O4 surface, forming adsorbed oxygen (O2(ads)). Subsequently, these adsorbed oxygen molecules capture electrons from the conduction band of the semiconductor, transforming into negatively charged oxygen species (O2(ads)). 2- (ads)).
[0071] O2(abs)+e - →O 2- (abs) (2)
[0072] As the number of negatively charged oxygen species increases, the electron concentration within the material decreases, leading to an increase in the resistance of the p-type semiconductor. This change in resistance is the basis for p-type semiconductor gas sensors to detect the presence of gases. Figure 5 This paper presents the band structure of NiCo2O4 and Ti3C2 MXene before contact. We measured the work function of Ti3C2 MXene, NiCo2O4, and the NiCo2O4 / Ti3C2 MXene composite by ultraviolet photoelectron spectroscopy (UPS). Work function (W) f ) through formula W f =hν-E cutoff The calculations show that hν represents the incident photon energy, and E cutoff The results were derived from the highest occupied molecular orbital (HOMO) in the UPS spectrum. Experimental results show that the binding energy peak of NiCo2O4 is located at 19.32 eV, and that of Ti3C2 MXene is located at 17.92 eV. Therefore, the calculated work functions are 1.9 eV for NiCo2O4 and 3.3 eV for Ti3C2 MXene, respectively. This indicates that the Fermi level of NiCo2O4 is higher than that of Ti3C2 MXene. After contact, electrons transfer from NiCo2O4 to Ti3C2 MXene, while holes move in the opposite direction, causing band bending (see...). Figure 5 b). Due to the transfer of these electrons, hole depletion layers and hole accumulation layers are formed on the surface of heterostructures in air. For example... Figure 5 As shown in c, oxygen molecules adsorb on the NiCo2O4 / Ti3C2MXene surface, capturing electrons from its conduction band to form chemisorbed oxygen species (O). 2- When reducing gas CO is introduced into the sensor environment, CO molecules first undergo physical adsorption on the surface of the NiCo2O4 / Ti3C2 MXene composite material, forming adsorbed CO(ads) (see...). Figure 5 d). Subsequently, the adsorbed CO molecules react with the previously formed negatively charged oxygen species (O). 2- (ads) undergoes a redox reaction to produce carbon dioxide (CO2(gas)) and releases electrons back into the conduction band.
[0073] CO(ads)+O 2- (ads)→CO2(gas)+e - (3)
[0074] Despite electron release, CO adsorption typically results in the occupation or trapping of more electrons. This is likely due to stronger interactions between CO molecules and the material surface, further increasing the material's resistivity. This change in resistivity is the opposite of that observed during oxygen adsorption, providing a feasible mechanism for CO gas detection. For this CO sensor, the main factors enhancing the sensing performance of the NiCo2O4 / Ti3C2MXene composite include: (i) the synergistic effect of the heterojunction between NiCo2O4 and Ti3C2MXene, (ii) a larger specific surface area, and (iii) Ni 2+ / Ni 3+ and Co 2+ / Co 3+ Ion pairs promote redox processes.
[0075] In-situ Raman spectroscopy analysis provides molecular-level insights into the CO sensing mechanism of the NiCo2O4 / Ti3C2 MXene heterostructure (see...). Figure 5 e). A significant spectral change was observed when exposed to 100 ppm CO at 110 °C: located at 312 cm⁻¹. -1 The characteristic Eg vibrational modes (related to in-plane vibrations of the carbon layer), and located at 456 cm -1 The Ni-O bond stretching vibration was observed. Upon introduction of CO, a significant shift in the Raman peak towards lower frequencies and a decrease in intensity were observed. This is due to the release of electrons by CO, leading to a decrease in the T... x The Ni-O bonds vibrate strongly. Importantly, the spectrum is fully recovered upon exposure to air, indicating that the chemisorption of CO at the heterostructure interface is reversible. This dynamic spectroscopic study demonstrates the reversible chemisorption and desorption of CO gas on the surface of the NiCo2O4 / Ti3C2 MXene heterostructure, providing a fundamental understanding of its rapid response and recovery properties.
[0076] Experiment Example 5: Construction and Application of CO Detection Equipment Based on UAV
[0077] Based on the excellent sensing performance of the MXene-based CO sensor, a portable gas sensor device was constructed, specifically designed for integration with small unmanned aerial vehicles (UAVs). Figure 6As shown in Figure a, the circuit diagram for the power management and voltage divider resistor measurement (IV) section reveals the core components and their interconnections. Through a carefully designed printed circuit board, we integrated the NiCo2O4 / Ti3C2 MXene sensor module with various electronic components to fabricate a prototype CO-sensitive gas sensor. The device mainly consists of two parts: a sensing section and a processing section. The sensing section includes a fixed terminal for the gas sensor and a 3V / 72mA heating circuit to maintain the sensor at its optimal operating temperature. The measurement circuit is a voltage divider resistor measurement circuit based on an AD8606 instrumentation amplifier, used to measure the voltage across a reference resistor. These signals are then transmitted to the ADC input pin of the STM32F4 microcontroller, which reads and processes these signals to achieve real-time monitoring of CO gas concentration. Notably, the entire sensor module is only 34 mm in diameter and weighs only 15 grams (including connectors), as shown in Figure a. Figure 6 The size comparison with a 1-yuan coin is shown in b. This compact design makes it ideal for integration into space-constrained devices such as drones. Figure 6 View c shows the top and bottom views of the drone, detailing its structural layout and the installation locations of key components. The top view shows that the drone employs a classic quadcopter design. The central area of the drone houses its core control unit, responsible for processing flight control algorithms and sensor data. The bottom view more clearly shows the sensor modules and power connections mounted on the drone. The sensor modules, mounted on the bottom of the drone, include a high-performance gas sensor for detecting specific gases in the environment, such as CO. The drone's battery serves as the primary power source, powering the sensor components. An XC6204 buck converter (see [link to system diagram]) is integrated into the system. Figure 6 a) It reduces the battery voltage to 3V to power the sensor's heating element and voltage divider measurement circuit.
[0078] Experimental evaluation of the CO sensing system mounted on a UAV demonstrated a high degree of integration between MXene-based detection capabilities and aerial maneuverability. For example... Figure 6 As shown in Figure d, this integrated experimental system combines a sensor-equipped quadcopter drone with stereo vision technology to achieve precise location and concentration distribution mapping of CO. A binocular camera provides real-time 3D environmental mapping, enabling precise location of the gas source through depth sensing and YOLOv8-based target tracking technology. The ground station simultaneously processes visual data and gas concentration readings from the drone, while the remote controller ensures flight stability. This integrated experimental design allows for comprehensive evaluation of the sensor's detection performance at different flight altitudes, distances, and angles. Figure 6The image shows a depth map, demonstrating that gas detection is distance-dependent. The color gradient visually represents the proximity of the drone to the CO source, corresponding to the measured resistance values (from 61.59 MΩ to 73.3 MΩ). As the drone approaches the gas source, the sensor's resistance increases due to the adsorption of gas molecules; conversely, as the drone moves away from the gas source, the resistance decreases due to the desorption of gas molecules. Figure 6 f depicts the flight trajectory of the UAV during a gas detection mission and the corresponding real-time resistance changes. The blue line depicts the complex trajectory of the UAV around the gas source, with each point representing its position at a specific time interval. The simultaneously recorded resistance values clearly demonstrate the adsorption / desorption behavior: resistance increases upon approach due to the adsorption of gas molecules; resistance decreases upon retreat due to the desorption of molecules, following the fundamental principles of gas-surface interactions. This UAV-based integrated sensing system successfully combines MXene-based gas detection with aerial maneuverability, establishing an effective three-dimensional environmental monitoring platform through synchronized visual mapping and chemical sensing capabilities.
[0079] In summary, this invention successfully designed and fabricated a high-performance carbon monoxide (CO) gas sensor for unmanned aerial vehicles (UAVs) based on NiCo2O4 / Ti3C2 MXene nanocomposite materials. Density functional theory (DFT) calculations and experimental verification revealed that the composite structure of NiCo2O4 and Ti3C2 MXene significantly enhances the adsorption capacity and reactivity for CO molecules. Experimental results show that the sensor exhibits a response value of approximately 139.5% to 100 ppm CO at 110 °C, with response and recovery times of 39 seconds and 234 seconds, respectively. Furthermore, the sensor demonstrates excellent selectivity and long-term stability. The superior performance of this composite material is attributed to the heterostructure formed between NiCo2O4 and Ti3C2 MXene, which not only increases the number of active sites but also promotes efficient electron transfer, thereby accelerating the kinetics of gas sensing. In addition, in-situ Raman spectroscopy further reveals the crucial role of the heterostructure in gas adsorption and reaction. Furthermore, this invention also discloses a gas monitoring system based on an unmanned aerial vehicle (UAV), which combines real-time 3D visual mapping with high-sensitivity detection capabilities to achieve accurate spatial quantification of CO distribution patterns. This invention achieves this through NiCo2O4 / MXene heterostructure design and UAV integration. Figure 7 This has pioneered a new approach to high-sensitivity gas detection, enabling intelligent environmental monitoring in fields such as industrial safety and air quality mapping.
[0080] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A CO detection device based on an unmanned aerial vehicle (UAV), characterized in that, The circuit board includes a CO sensor module, a power management module, a sensor heating module, and a voltage divider measurement module. The CO sensor module is made of NiCo2O4 / Ti3C2MXene composite material, and the voltage of the sensor heating module and the voltage divider measurement module is 3V.
2. The CO detection device based on a drone according to claim 1, characterized in that, The circuit board is a circular circuit board with double-sided copper plating, and the CO sensor module has a diameter of 34mm and a weight of 15g.
3. The NiCo2O4 / Ti3C2 MXene composite material contained in the UAV-based CO detection device as described in claim 1.
4. The NiCo2O4 / Ti3C2 MXene composite material according to claim 3, characterized in that, The composite material is a combination of bimetallic oxide NiCo2O4 and two-dimensional layered Ti3C2 MXene.
5. The preparation method of the NiCo2O4 / Ti3C2 MXene composite material as described in claim 3, characterized in that, First, multilayer Ti3C2T was prepared by acid etching. x MXene nanosheets were obtained, and then NiCo2O4 / Ti3C2MXene composite material was obtained through hydrothermal reaction.
6. The preparation method according to claim 5, characterized in that, The acid etching method was used to prepare multilayer Ti3C2T x Methods for using MXenes nanosheet materials include: (1) Add 40% hydrofluoric acid to the reactor, control the temperature and homogenize, then slowly add Ti3AlC2 powder to make the concentration of the reaction system 0.1g / mL, and stir to carry out the etching reaction; (2) After the etching reaction was completed, the black solution was centrifuged, the precipitate was washed with deionized water, the precipitate was dehydrated with ethanol, and dried to obtain multilayer Ti3C2T. x MXenes nanosheet materials.
7. The preparation method according to claim 5, characterized in that, The method for obtaining the NiCo2O4 / Ti3C2MXene composite material via hydrothermal reaction includes: Urea and NH4F were dissolved in n-butanol to form a homogeneous solution. Ni(Ac)2 and Co(Ac)2 were then added to the solution, followed by homogenization. During homogenization, 1-10 wt% Ti3C2T (based on the mass of NiCo2O4) was added dropwise. x After the MXenes material was completely dissolved, it was hydrothermally reacted at 180℃ for 18-20 hours. After cooling to room temperature, the precipitate was repeatedly washed with deionized water and anhydrous ethanol and dried to obtain the NiCo2O4 / Ti3C2 MXene composite material.
8. The preparation method according to claim 7, characterized in that, The mass ratio of urea to NH4F is 1:1, and the concentration of urea in the n-butanol solution is 25 mg / mL; the molar ratio of Ni(Ac)2 to Co(Ac)2 is 1:2, and the ratio of the total mass of Ni(Ac)2 and Co(Ac)2 to the total mass of urea and NH4F is 1:2.